2020
DOI: 10.1088/1361-665x/ab9f46
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, test, calibration and modeling of a temperature-actuated hydrogel bilayer

Abstract: Smart structures such as temperature-sensitive actuators made of soft hydrogels can be useful for designing biomedical devices. In this study, free swelling and force generation behavior of a bilayer actuator based on thermo-sensitive poly(N-isopropylacrylamide) (PNIPAM) hydrogel and an elastomer under various loading profiles has been investigated. The thermo-sensitive hydrogel was synthesized by redox-initiated radical polymerization. We then prepared a bilayer actuator made of temperature-sensitive PNIPAM h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Thermo-responsive hydrogel bilayers incorporating PNIPAAm as its thermosensitive element have been previously reported in literature and are generated by either forming one layer on top of another after complete gelation of the former or by adhering two layers together using an adhesive. [65][66][67][68][69] These bilayers are often employed as actuators in solutions that bend as the temperature exceeds the LCST of PNIPAAm. The PNIPAAm-co-PAAm-co-RHO precursor had a lower density than the PAAm-co-FOA precursor so we designed the mold such that the less dense precursor could enter from above and the denser precursor could enter from below (Figure 4c ii).…”
Section: Synthesis Of 3d Hydrogel Systemsmentioning
confidence: 99%
“…Thermo-responsive hydrogel bilayers incorporating PNIPAAm as its thermosensitive element have been previously reported in literature and are generated by either forming one layer on top of another after complete gelation of the former or by adhering two layers together using an adhesive. [65][66][67][68][69] These bilayers are often employed as actuators in solutions that bend as the temperature exceeds the LCST of PNIPAAm. The PNIPAAm-co-PAAm-co-RHO precursor had a lower density than the PAAm-co-FOA precursor so we designed the mold such that the less dense precursor could enter from above and the denser precursor could enter from below (Figure 4c ii).…”
Section: Synthesis Of 3d Hydrogel Systemsmentioning
confidence: 99%
“…The polymer layers are typically hydrogels where the active layer swells more than the passive layer resulting in bending toward the passive layer. The swelling can be solvent (i.e., water)-, temperature-, pH-, electric-field- or ionic strength-induced. Folding into more sophisticated final shapes can be achieved via photopatterning, lithography, or 3D printing (for 4D printing). Seedpod-like twisting has also been mimicked by imparting orientational order into polymer and elastomeric bilayers to generate solvent - or temperature -induced twisting, as well as pH-, ionic strength-, and light-induced shape change. Some highly engineered materials can respond to multiple stimuli such as temperature and solvent, photothermal or electro-thermal, and UV light, NIR, solar, and heat .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the researchers found that the actuate membrane materials including sodium alginate [8] , cellulose, chitosan [9][10][11][12] . Due to their unique three-dimensional network structure and ability to retain a large amount of water, ion actuator had a wide range of applications in hydrogel arti cial muscles [13] including biomedical applications, drug carriers [14][15] , biosensors [16] , medical devices [17] , tissue engineering [18] , separation systems [19][20] , micro uidic systems [21] , microvalves [22] and actuator [23][24] . Chitosan (CS) was a product of natural chitin.…”
Section: Introductionmentioning
confidence: 99%